Pengaruh Bantuan Sosial (BPNT, KIP, KIS) terhadap Indeks Pembangunan Manusia di Kabupaten/Kota Provinsi Papua Tahun 2018-2022 - Ilvi Nur Diana; Renta Yustie (Universitas Nusantara PGRI Kediri, 2025)
The purpose and intent of the researcher in this study is to test and see the analysis of the influence of social assistance programs on the Human Development Index. The types of social assistance programs used are BPNT, KIP, and KIS as independent variables and HDI as the dependent variable. The types of social assistance programs taken are in line with the Human Development Index indicators according to UNDP, namely indicators of healthy living, well-educated, and having a good standard of living. The analysis of this study uses saturated samples using districts/cities in Papua Province, namely 29 districts/cities. This study uses multiple linear regression methods accompanied by classical assumption testing and hypothesis testing. The results of the analysis show that the Non-Cash Food Assistance Program (BPNT) has a positive and significant impact on the Human Development Index (HDI). Conversely, the Smart Indonesia Card (KIP) shows a negative but significant impact on the HDI, while the Healthy Indonesia Card (KIS) has a negative but not significant impact on the HDI.